Ruthless bastards [videorecording (DVD)] - Jhattu, Varinder; Flanery, Sean Patrick; Verma, Parmish; Kaur, Hasleen; Van Dien, Casper, 1968- (Darkstar Pictures, 2025)
Former hitmen Nico and Rick reunite for one last job to take down a rising crime lord, Sunny Gill. With a $5 million pay-day on the line, they must set aside their rivalry to collect assuming they don't kill each other first.